Unusual presentation of Diphyllobothrium pacificum: a case of ileitis mimicking lymphoma - Chávez-Sánchez, Siomara Aransuzú (2024)
Diphyllobothrium spp. is a parasite with global distribution. Diphyllobothriasis is the human infestation by this parasite. Symptoms usually occur a few weeks after infection and include nausea, diarrhea, and abdominal pain; less frequently, prolonged or severe infections can lead to anemia. The endoscopic finding of the tapeworm is an incidental finding. The inflammation associated with diphyllobothriasis can be considered in the differential diagnosis of ileal ulcers. We present the case of a woman in whom a tapeworm and one ileal ulcer were found, histology suggested lymphoid proliferation; however, the clonality study showed that these inflammatory changes were secondary to diphyllobothriasis.